Peningkatan Good Governance Melalui Penerapan Kaizen - Putri Nurmala; Akhmad Sigit Adiwibowo (Abdimisi, 2020)
Kaizen literally means "Improvement". This understanding gives broad meaning to the application of Kaizen in everyday life. The Kaizen concept is defined as continuous improvement with 5 (five) foundations, namely group activities, discipline, moral development, quality control, and suggestions for improvement that come from all relevant parties. Seeing this we consider the importance of Kaizen being applied in schools. One application of Kaizen is the preparation of financial reports, which in SDIT Al Inayah there are no financial reports. This certainly has an impact on the going concern of the school. The method of implementation was carried out with the first survey related to what was needed by the Al Inayah SDIT. It turns out that what is needed by SDIT Al Inayah is in line with our PKM theme, which is the preparation of financial reports. After that, for five weeks every week, twice, our team helped make financial reports in July-September 2019 SDIT Al Inayah by using an application system, which previously was still manual in several books. The result of this PKM is the realization of SDIT Al Inayah's financial reports in the application system for July-September 2019. In addition, SDIT Al Inayah now also understands the importance of making relevant and accountable financial statements.